MANAJEMEN KESISWAAN PADA SEKOLAH DASAR - Aliyyah, Rusi Rusmiati; Widyasari, Widyasari; Mulyadi, Didi; Ikhwan, Subaiki; Prananosa, Ahmad Gawdy (Universitas Djuanda, 2019)
This research aims to get the pattern of student management in Elementary Schools (SD) according to the Graduates Competency Standards (SKL). The study was conducted at Pertiwi Elementary School in Bogor city using qualitative methods with the type of case study research. Data collection techniques are carried out through interviews, observation, and documentation. Data analysis uses the Miles and Huberman Model which consist of data collection, data reduction, data presentation and verification or conclusion. Examination of the validity of the data using triangulation. The results showed: (1) Management of students was carried out starting from planning, student admission, student orientation, grouping / placement of students, reporting of evaluation results, level and non-level systems, mutations and drop out of students, special services for students, disciplinary coaching of students, student organizations, and graduations and alumni. (2) Teachers become pioneers in the management of students because they have an agent role in the progress of students' development.